Hypozincemia in COVID-19 Patients Correlates With Stronger Antibody Response - Xu, Wenye; Liu, Yingzhi; Zou, Xuan; Luo, Huanle; Wu, Weihua; Xia, Junjie; Chan, Matthew T. V.; Fang, Shisong; Shu, Yuelong; Wu, William K. K.; Zhang, Lin (Frontiers in Immunology, 2022)
Zinc ion as an enzyme cofactor exhibit antiviral and anti-inflammatory activity during infection, but circulating zinc ion level during Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection is unclear. This study aimed to evaluate serum zinc ion level in Coronavirus Disease 2019 (COVID-19) patients and healthy subjects, as well as its correlation with antibodies against SARS-CoV-2. 114 COVID-19 patients and 48 healthy subjects (38 healthy volunteers and 10 close contacts of patients with COVID-19) were included. Zinc ion concentration and levels of antibodies against SARS-CoV-2 Spike 1 + Spike 2 proteins, nucleocapsid protein, and receptor-binding domain in serum were measured. Results showed that the concentration of zinc ion in serum from COVID-19 patients [median: 6.4 nmol/mL (IQR 1.5 – 12.0 nmol/mL)] were significantly lower than that from the healthy subjects [median: 15.0 nmol/mL (IQR 11.9 – 18.8 nmol/mL)] (p < 0.001) and the difference remained significant after age stratification (p < 0.001) or when the patients were at the recovery stage (p < 0.001). Furthermore, COVID-19 patients with more severe hypozincemia showed higher levels of IgG against the receptor-binding domain of SARS-CoV-2 spike protein. Further studies to confirm the effect of zinc supplementation on improving the outcomes of COVID-19, including antibody response against SARS-CoV-2, are warranted.